Reasons for the Frequent Use of the Emergency Service by the Elderly in the Context of a Family Health Unit - Idalina Delfina Gomes (2021)
The world population is aging, which leads to an increase in chronic diseases and an increased risk of frailty, with implications for the frequent use of the emergency department by the elderly, with an impact on social and health levels, which should be a concern for nurses who need to intervene in promoting the health of this population; Goals: analyse the reasons for the frequent use of the emergency department by the elderly; Method: qualitative descriptive study, using semi-structured interviews and content analysis; participants - 6 (frail elderly and family caregivers); Results: it was found that most of the reasons that led the participants to make use of emergency department were related to periods of acute of the chronic disease(s), search for specialized care, referral by healthcare professionals, fear of worsening the disease and difficulty in accessing the primary healthcare facility; Conclusions: primary healthcare nurses need to invest more in the surveillance of chronic diseases(s) and promote the literacy of the elderly and the family caregiver to promote the Self-Care.